Secondary subfertility among the couple attending selected fertility centre of Dhaka, Bangladesh - Bari, Sumia; Begum, Mosammat Shahina; Nessa, Kamrun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Couple suffering from secondary subfertility is a major health concern. Pattern involved both the male and female factors and sometimes unknown aetiology. This cross-sectional study was carried out to see the pattern of secondary subfertility among the couples attended selected fertility centres of Dhaka city to ascertain the risk factors. Methods: A cross sectional study was carried out among the couples attended from September 2011 through March 2012. There were 190 couples were interviewed with questionnaire using the purposive sampling method and analyzed by SPSS 20. Results: Among the 190 couples suffering from secondary subfertility, 52% cases female factors, 13% male factors, unexplained 27% and both male and female factors lie behind 8% of cases. Among the female causes 31% were tubal factors, 26% cases PCOD, ovulatory disorders and endometriosis 21% and 22% respectively. Result revealed that the mean age of the female was 32 and 54% were obese. The women who had tubal factors had H/O MR or D&C in significant number. Female age, weight menstrual irregularity, medical disorders and number of previous abortion were significantly correlated with secondary subfertility .Among the male factors 76% cases shows abnormal semen parameters, 12% cases coital problem, 12% cases ejaculatory problem due to chronic disease like chronic HTN, DM. Conclusions: This study concluded that proper evaluation with details personal, medical and gynaecological history of female and also male factors need to evaluate the cause and formulate a management plan to treat the secondary subfertile couple.